Relationships among nutrition knowledge level, healthy eating obsessions, body image, and social media usage in females: a cross-sectional study - Sahin, Elif; Sanlier, Nevin (BMC public health, 2025)
This study examined the relationships among female's nutrition knowledge levels, diet practices, healthy eating obsessions, body perceptions, and social media usage. The study included 613 voluntarily participating females aged 18-60 years. Data including demographic information, anthropometric measurements, whether they follow a diet or not, and ORTO-R, Body Shape Questionnaire (BSQ-34), Bergen Social Media Addiction Scale (BSMAS), and General and Sport Nutrition Knowledge (GeSNK) Scale scores were collected. The participants' mean age was 28.47 ± 9.38 years. Mean scores were 17.5 ± 5.1 for the ORTO-R scale, 89.2 ± 40.2 for the BSQ-34, 38.6 ± 12.5 for the GeSNK, and 17.3 ± 6.1 for the BSMAS. Statistically significant differences were found among the participants' total ORTO-R, BSQ-34, and GeSNK scores according to body mass index (BMI) and education level. Statistically significant relationships were also found among total ORTO-R, BSMAS, BSQ-34, and GeSNK scores. ORTO-R scores were positively correlated with BSMAS (r = 0.475, p < 0.05) and BSQ-34 (r = 0.685, p < 0.05) scores, while they were negatively correlated with GeSNK scores (r = -0.117, p < 0.05). There was a positive correlation between BMI and BSQ-34 scores (r = 0.380, p < 0.001) and between BMI and ORTO-R scores (r = 0.130, p < 0.001), while there was a negative correlation (r = -0.176, p < 0.001) between BMI and GeSNK scores. Social media is a fast, important, and effective tool for the sharing of information. Thus, social media may be effective in strengthening individuals' nutrition knowledge, nutrition obsessions, body perceptions. Therefore, it would be beneficial to provide training for individuals to use social media consciously and providing nutritional literacy will be effective.